Idiopathic Musculoskeletal Pain and Stress Factors - J Gordon Millichap (Pediatric Neurology Briefs)
The role of psychosocial factors was evaluated in 23 children with idiopathic musculoskeletal pain (IMP) and 52 with juvenile chronic arthritis (JCA), compared on admission and at 9 year follow-up, in a study at The National Hospital, Oslo, Norway.